AgNP-AC Composite Fibers and its Adsorption and Antibacterial Properties - Liu, Dandan; Zhang, Chuanwei; Wang, Bin; Quan, Wenwen; Xu, Chao (Frontiers in Materials, 2022)
In this study, the electrospinning method was used to prepare silver nanoparticles activated carbon (AgNPs-AC) composite nanofiber membranes, aiming to obtain a high-performance dual functional filter composite fiber membrane with good antibacterial and adsorption properties. Scanning electron microscope (SEM), X-ray diffraction (XRD) and other instruments were used to characterize the morphology and structure of the composite nanofibers. The effects of different concentrations of the activated carbon, silver and polymer (polyethylene-vinyl alcohol - EVOH) on the fiber morphology were discussed. The adsorption performance and antibacterial performance of the composite fiber membrane were investigated to verify the mutual influence of silver and activated carbon. Results show that with the increase of activated carbon and silver concentration, fiber diameters of AgNPs-AC membrane increase and the diameter distribution tends to become uniform. When the mass fraction of polymer EVOH is 10% and the concentration ratio of silver nitrate and carbon is 0.05 and 0.085 (g/mL), the adsorption performance of the composite fiber membrane is at the best with an adsorption rate of 94.07%. The AgNPs-AC composite nanofiber membrane also demonstrates good antibacterial function against Staphylococcus aureus and is most effective in first 8 hours. However, it is found that the silver concentration is proportional to the antibacterial ability but the activated carbon has a certain inhibitory effect on the antibacterial properties.